Contribution of legumes on phosphoric absorption by Panicum maximum cv Riversdale in intercropping system - Sajimin .; Nurhayati D. Purwantari; Irawan Sugoro (Jurnal Ilmu Ternak dan Veteriner, 2016)
Phosphorus availability in soil as a mobile mineral influences forage growth. The purpose of doing this research is to enhance the soil phosphorus availability and grass production of Panicum maximum cv Riversdale by intercropping system with legums. The experiment was conducted based on with randomized design with five treatments of mixcropping of: (i) Gliricidia sepium + P. maximum; (ii) Calliandra calothyrsus + P. maximum; (iii) Leucaena leucocephala cv Taramba + P. maximum; (iv) Calopogonium mucunoides + P. maximum; (v) P. maximum as negative control. Plants were grown in pots with split-root technique using partition with a whole to allow some legume roots grew in the grass side. After growing for three months, on the legume areas 32P isotop solution was injected for 50 ml (11.23 μci/ml). After 21 days incubation samples were collected from both soil areas and both plants. The translocation of 32P was determined using geiger counter from legumes into the grass and the concentration of 32P was also determined in all plants. Forage productions was determined both in the legumes and grass. Result showed that soil phosphorus concentration in the grass area was significantly improved by intercropping with G. sepium and C. callothyrsus, while the one with L. leucocephala was similar, and the one with C. mucunoides was significantly lower than that of negative control (without legume). Detection of 32P showed that there was P translocation in the system. P. maximum grass production depending on kind of legumes (P<0.05) those with G. sepium was significantly higher, L. leucocephala and C. callothyrsus were not significantly higher, while the one with C. mucunoides was 26.2% lower from the control although not significantly. However, C. mucunoides produced the highest forage from the legume plant. It is concluded that grass-legume intercropping had a positive impact on phosphorus soil concentration in the grass area and grass production. Kind of legumes influenced the effectivity.